COVID-19 economic shocks and fiscal policy options for Ghana. Issue 5 (30th October 2020) - Dzigbede, Komla D.; Pathak, Rahul
Abstract : Purpose: This article examines the fiscal challenges the coronavirus pandemic poses in African countries, using Ghana as a case study and summarizes the country's immediate monetary and fiscal responses to the pandemic. The article also discusses the potential impacts of coronavirus-related shocks on the Ghana economy and policy options the national government may pursue to counteract the pandemic's adverse long-term effects. Design/methodology/approach: The article uses daily and monthly economic indicators to assess the immediate impact of the pandemic on Ghana's economy. The article also uses latest data from the Ghana Living Standards Survey (GLSS) to simulate potential shocks to the economy related to the coronavirus crisis and examines the outcomes from a potential government response that expands spending on an existing direct social assistance program. Findings: The authors find that the coronavirus pandemic is associated with a significant increase in Ghana's poverty measures over time, and an expansion in government spending under an existing cash transfer program would partly offset the economic shocks related to the crisis and improve outcomes for poverty and inequality. The authors also argue that other well-targeted expenditure and revenue policies will support long-term economic resilience. Research limitations/implications: The research suggests that a temporary expansion of the existing program of direct cash payments to poor households may be an effective social protection policy, as are well-targeted revenue and spending policies that support economic recovery and long-term fiscal sustainability. Practical implications: The findings imply that while the pandemic might cause severe shocks in the economy, well-targeted spending and revenue policies that are anchored in sound macroeconomic management can promote economic resilience and long-term fiscal sustainability. Social implications: Public managers must ensure that national policy responses to the coronavirus pandemic consider socio-economic indicators, such as poverty and income inequality. Originality/value: The authors present research that uses novel household-level data and an evidence-based microsimulation framework to articulate potential public policy strategies that can guide national responses to, and recovery from, the coronavirus pandemic.